2010
DOI: 10.1186/1471-2334-10-127
|View full text |Cite
|
Sign up to set email alerts
|

The burden and risk factors of Sexually Transmitted Infections and Reproductive Tract Infections among pregnant women in Zimbabwe

Abstract: BackgroundSexually transmitted infections (STIs) and Reproductive tract infections (RTIs) are responsible for high morbidity among women. We aim to quantify the magnitude of the burden and risk factors of STI/RTI s among pregnant women in Zimbabwe.MethodsA cross sectional study of pregnant women enrolled at 36 weeks of gestation from the national PMTCT program. Study was conducted from three peri-urban clinics around Harare Zimbabwe offering maternal and child health services.ResultsA total of 691 pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
8
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 18 publications
5
41
8
2
Order By: Relevance
“…Differences in the infection rates were not significant among different education levels, income levels and occupation. Similar to other studies, increased rate of the infection was associated with raising age (11). This may be due to more sexual contact with increasing age.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Differences in the infection rates were not significant among different education levels, income levels and occupation. Similar to other studies, increased rate of the infection was associated with raising age (11). This may be due to more sexual contact with increasing age.…”
Section: Discussionsupporting
confidence: 75%
“…Some comparative studies showed that the pregnant women with trichomoniasis have 30% higher risk of delivering baby with low birth weight or delivering preterm than those without the infection (26). Also more prevalence of some STIs has been reported from pregnant women in some areas (11,29); alteration of vaginal flora during pregnancy may be of relevant consecutive concerns (30). These indicate the importance of trichomoniasis in this group of women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPIUD expulsion, missing strings, infection and its other complications are minimal when the IUD is inserted aseptically by a skilled provider with proper techniques and by placing the device in the uterine fundus [18]. The higher incidence of untreated reproductive tract infections in many developing countries is a serious concern in the provision of PPIUD [19,20]. The use of prophylactic antibiotics was suggested by Muthal-Rathore [21] in prolonged labour and prolonged rupture of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In our study the history of sexual transmitted infections and received treatment was 14.5% compared to 25% in a study in Zimbabwe [12].…”
Section: Discussionmentioning
confidence: 90%